(untitled) (Research, Society and Development, 2022)
Objective: to synthesize the scientific production on mobile applications in the promotion of breastfeeding. Method: this is an integrative literature review carried out in Medline/PubMed, Scopus, LILACS, Web of Science databases and in the Cochrane library. The search was carried out in January 2022 using combinations from the descriptors: mobile applications; breastfeeding; health technology and health education. Results: 171 articles were identified and of these 12 were selected due to the relevance of the research topic and methodological rigor. Descriptive studies and randomized controlled clinical trials were examined that addressed the use of mobile applications designed to analyze feelings and experiences of nursing mothers, as well as an information tool in order to promote better rates related to the breastfeeding process. Conclusion: Mobile applications, as a strategy and instrument of communication and promotion of breastfeeding, are showing great growth at the same time that technological applications invade people’s routine.